2005
DOI: 10.1002/eji.200526181
|View full text |Cite
|
Sign up to set email alerts
|

Post-thymic in vivo proliferation of naive CD4+ T cells constrains the TCR repertoire in healthy human adults

Abstract: In spite of thymic involution early in life, the numbers of naive CD4 + T cells only slowly decline in ageing humans implying peripheral post-thymic naive CD4 + T cell expansion. This proliferation may compensate for continuous activation and death of naive CD4 + T cells but may also have negative consequences for protective immunity. Here we show that naive CD4 + T cells that have proliferated in the periphery are characterized by a highly restricted oligoclonal TCR repertoire. Additionally these cells, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
128
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(146 citation statements)
references
References 32 publications
14
128
1
3
Order By: Relevance
“…13,17 Since the absolute number of thymic naïve CD4 + T cells in the peripheral blood of healthy volunteers is low, it was vital to validate the usefulness of CD31 as a marker for RTE. As previously demonstrated by others, 17,19 the number of CD3 + CD4 + CD45RA + CD31 + T cells was inversely correlated with age and showed a good correlation with the sjTREC. The concomitant study of Ki67 expression revealed a very low amount of proliferation in the thymic naïve subpopulation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…13,17 Since the absolute number of thymic naïve CD4 + T cells in the peripheral blood of healthy volunteers is low, it was vital to validate the usefulness of CD31 as a marker for RTE. As previously demonstrated by others, 17,19 the number of CD3 + CD4 + CD45RA + CD31 + T cells was inversely correlated with age and showed a good correlation with the sjTREC. The concomitant study of Ki67 expression revealed a very low amount of proliferation in the thymic naïve subpopulation.…”
Section: Discussionsupporting
confidence: 81%
“…16,17 Over the past 10 years, many groups have used the quantification of single-joint (sj) T-cell receptor excision circles (sjTREC) by quantitative polymerase chain reaction (QT-PCR) in various subpopulations in the peripheral blood as a surrogate markers for RTE. [18][19][20][21][22] sjTREC are formed during the rearrangement of the α-chain of the T-cell receptor in the thymus. This approach has proved to be valuable but it is limited by the fact that lymphocyte proliferation induced by antigen and/or cytokines results in a dilution of sjTREC since they are not replicated in the cell cycle.…”
Section: ©2013 Ferrata Storti Foundation This Is An Open-access Papementioning
confidence: 99%
“…In HIV patients the CD31C thymic naive CD4C cells depletion is more evident than in age-matched healthy controls: this process may explain at least part the reduced TCR repertoire and the consequent detrimental response to neoantigens (infections, cancer, autoimmunity, vaccinations). 34,35 Moreover, in older HIV-infected patients (> 50 years) the compensatory increase of CD31-centralnaive CD4C cells is also reduced compared both to agematched controls and to younger HIV patients. 6,36 The synergistic action of age and HIV infection explain the faster progression to AIDS in older people infected with HIV 6,35,36 .…”
Section: Immunology Of Aging In Hiv-infected Patientsmentioning
confidence: 99%
“…CD31 ϩ naive CD4 T cells are most proximal to the thymus (41) and have been described to have a much more diverse TCR repertoire than CD31 Ϫ naive CD4 T cells (41,42). During aging, the percentage of CD31-expressing naive CD4 T cells has been shown to decrease (41), raising the question of whether the fraction of CD31-expressing naive CD4 T cells, and thereby normal levels of naive T cell repertoire diversity, can be attained during immune reconstitution.…”
Section: Normal Fraction Of Cd31-expressing Naive Cd4 T Cells After Lmentioning
confidence: 99%
“…During aging, the percentage of CD31-expressing naive CD4 T cells has been shown to decrease (41), raising the question of whether the fraction of CD31-expressing naive CD4 T cells, and thereby normal levels of naive T cell repertoire diversity, can be attained during immune reconstitution. To determine whether CD4 T cell recovery was associated with accelerated aging of the naive T cell compartment, the fraction of CD31 ϩ cells was determined within the naive CD4 T cell compartment after long-term HAART.…”
Section: Normal Fraction Of Cd31-expressing Naive Cd4 T Cells After Lmentioning
confidence: 99%